6 The role of a novel angiogenesis related protein, FKBPL, in spiral uterine artery remodelling important for the pathogenesis of preeclampsia. (26th March 2018) - McNally, Ross; Todd, Naomi; Alqudah, Abdelrahim; Robson, Tracy; Grieve, David; McClements, Lana
Abstract : Introduction: Preeclampsia is a complication which occurs in 5%–6% of pregnancies, characterised by high blood pressure and/or other organ dysfunction in the third trimester of pregnancy. Preeclampsia has short-term risks for the mother and child, but is also associated with remote cardiovascular disease and/or type 2 diabetes mellitus in both. The pathogenesis of preeclampsia is unclear but it appears to be attributed to inappropriate remodelling of spiral uterine artery as a result of dysregulated trophoblast function. We investigated the involvement of novel regulator of developmental and pathological angiogenesis, FKBPL, and its role in the pathophysiology of preeclampsia. Methods: Trophoblast cells (HTR8.SV.neo, BeWo and JAR) were exposed to hypoxic (1%) or normoxic (21%) conditions before wound scratch migration assays were performed, and FKBPL protein levels measured. BeWo cells were treated with the HIF-1α activator, DMOG, for 24 hour before protein lysates were extracted for western blotting analysis. Colony forming efficiency and the number of holoclones, meroclones and paraclones of both HTR8.SV.neo and JAR trophoblast cells were determined in the presence of hypoxia or normoxia via clonogenic assay. Results: BeWo and JAR migration increased by approximately 40% following 24 hour exposure to hypoxia (n=6; BeWo, p<0.05; JAR, p<0.01), and FKBPL protein expression was downregulated (n=3; HTR8.SV.neo, p<0.01; BeWo, p<0.05; JAR, p<0.01), when compared to normoxia. DMOG treatment downregulated FKBPL protein levels in BeWo cells (n=3, p<0.01). JAR colony formation was reduced by approximately 70% in hypoxia (n=3, p<0.01); all colonies appeared to be holoclones. No change in colony formation was observed in HTR8.SV.neo cells; however, there was over two-fold reduction of holoclones, and an increase in differentiated colonies, meroclones plus paraclones (n=3, p<0.05). Conclusion: Our in vitro data suggest that FKBPL plays an important role in trophoblast functionality, which may extend to spiral uterine artery remodelling underlying the pathogenesis of pre-eclampsia.